Estimating shear wave velocity (Vs30) of East Java, Indonesia, using ambient noise inversion of horizontal to vertical spectral ratio (HVSR). Issue 1 (July 2020) - Tawakal, M I; Haris, A; Martha, A A
Abstract: The shear wave velocity on average to a depth of 30 m (Vs30) is an important parameter for seismic hazard assessment. Vs30 can identify soil dynamic characteristics that can be used to seismic hazards mitigation efforts. East Java is one of the provinces in Indonesia that has high geological disaster potential. Therefore, a study of earthquake risk mitigation strategies must be carried out as a disaster mitigation effort. One of the ways to determine soil characteristics is to estimate the shear wave velocity. This study aims to determine the average shear wave velocity (Vs30) to obtain information on the vulnerability of soil conditions in East Java. we use stationary seismograph data from Indonesian Agency for Meteorology, Climatology, and Geophysics (BMKG), German Research Centre for Geosciences (GFZ) temporary seismograph and secondary data from seismic waveform portable seismographs installed independently in East Java. This study uses the horizontal and vertical ambient noise inversion method. One-dimensional wave velocity models are obtained from Monte Carlo simulations based on the best misfit values. Vs30 East Java values ranged from 168–788 m/s with sediment thickness ranging from 10 meters to more than 200 meters. Based on the classification of soil types, in the northern part of East Java is dominated by the type of soft soil (SE) to hard soil (SC). In the southern part of eastern Java is dominated by medium soil (SD) to hard rock (SA). The northern part of East Java, especially in the Kendeng zone is dominated by low shear wave velocity. Lowest Vs30 can be seen in Sidoarjo, Surabaya, Mojokerto, Jombang, Gresik, Lamongan, Nganjuk, Madiun, Ngawi, Bojonegoro, Probolinggo and the southern part of the Madura Island. The low shear wave velocity (Vs30) is associated with sediment layers and high shear wave velocity (Vs30) is associated with hilly areas and transition zones.